Synthesis of Polyvinyl Pirrolidone (PVC) /Κ-Carrageenan Hydrogel Prepared by Gamma Radiation Processing As a Function of Dose and PVP Concentration - Erizal Erizal; Tjahyono Tjahyono; Dian PP; Darmawan Darmawan (Universitas Gadjah Mada, 2013)
The aim of this research is to prepare a biomaterial to be used in health care. A series of hydrogels based on polyvinyl pyrrolidone (PVP)/κ-Carrageenan (KC) has been prepared by radiation technique. PVP (5-15%) were mixed with ΚC (2%) and irradiated by gamma rays at the doses from 25 kGy to 35 kGy (dose rate 7 kGy/h) at room temperature. The chemical change of hydrogels was characterized using Fourier Transform infra Red (FTIR). Gel fraction, water absorption and water evaporation were determined gravimetrically. Tensile strength and elongation at break was measured using Instron meter. It was found that with the increase irradiation dose and PVP concentration, the gel fraction and tensile strength of hydrogels increase. In contrast the elongation at break and water absorption of hydrogels decrease. The hydrogel of PVP/KC hydrogel produced by gamma radiation can be considered for wound dressings.